Shaping the university imaginary : configurations and refigurations in British fiction - Seligardi, Beatrice; Justus Liebig University Giessen (My University, 2014)
The present work stems from the attempt to deal with the literary representations of the university imaginary by focusing on mimesis. The first part of the present study investigates the forms taken by university fiction in the British context from the 19th century until the second half of the 20th, a period when the genre achieved specific and stable connotations that have been respectively classified as varsity novel and campus novel. The second part deals with what happens when the university imaginary and its representation go beyond the boundaries of university fiction as a genre. The case study proposed is constituted by the novels of the British writer A.S. Byatt. This case study allows us to analyse a different way in which the university imaginary has been configured, a way that is, of course, related to literary genres, but which also goes beyond the typical boundaries of genres as literary constructs. This re-figuration has been explained by resorting to a concept that originally came from theatre and adaptation studies, but which proves to be productive when applied to narrative texts: the concept of dramatisation . A narrower definition of the term is provided in order to embrace specific mimetic and diegetic strategies. Moreover, the comparison between university fiction and dramatisation, as regards processes of worldmaking, sheds light on how literary configuration is always subjected to processes of reconfiguration, which take shape through new strategies of representation and literary forms.
Keywords: ddc:820